2020
DOI: 10.1007/jhep06(2020)017
|View full text |Cite
|
Sign up to set email alerts
|

An entropy current for dynamical black holes in four-derivative theories of gravity

Abstract: We propose an entropy current for dynamical black holes in a theory with arbitrary four derivative corrections to Einstein's gravity, linearized around a stationary black hole. The Einstein-Gauss-Bonnet theory is a special case of the class of theories that we consider. Within our approximation, our construction allows us to write down a completely local version of the second law of black hole thermodynamics, in the presence of the higher derivative corrections considered here. This ultra-local, stronger form … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(75 citation statements)
references
References 33 publications
11
64
0
Order By: Relevance
“…2 The context and the backdrop of our current work. Our analysis in this paper is significantly motivated and based on the important results that were reported recently in [14] and subsequently in a follow-up paper [22]. Therefore, to better understand the context of this current paper, it is useful and informative that we discuss them a priori.…”
Section: Jhep09(2021)169mentioning
confidence: 97%
See 3 more Smart Citations
“…2 The context and the backdrop of our current work. Our analysis in this paper is significantly motivated and based on the important results that were reported recently in [14] and subsequently in a follow-up paper [22]. Therefore, to better understand the context of this current paper, it is useful and informative that we discuss them a priori.…”
Section: Jhep09(2021)169mentioning
confidence: 97%
“…Although we would have nothing to say about those situations within this paper's premise, see [19][20][21] where a similar problem has been studied with exciting conclusions. 3 For a detailed discussion the reader is requested to see section 2 of [22] where a comprehensive review of [14] is given.…”
Section: Jhep09(2021)169mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of this paper used the physical process version of first law to arrive at this correction. The authors of [18] then showed that the requirement of physical process first law can be relaxed by correctly capturing the presence of a spacial entropy current on the horizon along with the entropy density derived in [16,17]. In a different context the authors of [19] found a correction to the Wald entropy which satisfies the second law for non-linear but spherical dynamics of black holes.…”
Section: Introductionmentioning
confidence: 99%